Amyand’s hernia: an uncommon entity - Silva-Zamora, Jorge; Romero Macias, Arturo; Baigts Arriola, Luis A.; Dámazo Escobedo, Cristian A.; Vizcarra Rendón, Adriana G.; Sevilla Flores, Jose G. (International Journal of Research in Medical Sciences, 2024)
A 60-year-old male case whose condition began 6 months prior to admission to the emergency department, presenting an increase in volume in the right inguinal region, with intermittent pain, colic type, with an intensity rating of 8-10/10. On physical examination we found increased volume in the right inguinal region when standing, tumor measuring approximately 5x5 cm, hernia defect approximately 4 cm in diameter, non-painful and reducible. Patient was diagnosed clinically as direct right inguinal hernia and ultrasound confirmed the diagnosis with the presence of the appendix in the sac. A pre-operative diagnosis of right inguinal hernia was made and was planned for hernia mesh repair, during surgery under spinal blockage, the hernia sac was found to contain an appendix without signs of inflammation, so we decided to close the defect and repair with a Lichtenstein mesh hernioplasty without doing an appendectomy. In this case we treated a rare clinical entity called Amyand’s hernia. This case highlights the importance of considering Amyand’s hernia in the differential diagnosis of inguinal pathologies and the role of imaging modalities in pre-operative diagnosis. Various classification systems have been proposed, including those by Losanoff and Bason, later modified by Rikki et al offering insights into surgical management strategies based on the condition of the appendix and concomitant pathologies. Despite efforts to standardize treatment approaches, consensus on the optimal management strategy remains elusive, necessitating further research to refine diagnostic and therapeutic guidelines.